2021
DOI: 10.1038/s41598-021-85861-8
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of salivary properties of pre-orthodontic patients in relation to age and sex

Abstract: Saliva plays an important role in masticatory function and protection from dental caries. Although studies have been conducted on saliva properties, their results vary widely depending on population settings. Hence, this study was performed to evaluate the results of saliva properties in individuals who attended their first visit for orthodontic treatment. A total of 619 participants were included (387 females and 232 males; mean age: 14.6 years). We conducted oral examinations and saliva (stimulated) tests an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Additionally, 1373 full-text reports were not accessible among the 25 full-text articles we assessed for eligibility, 18 studies were subsequently excluded. 3 , 6 , 8 , 10 , 12 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 Finally, 7 studies were included in a systematic review. 2 , 11 , 15 , 16 , 17 , 18 , 19 An overview of the search results and the screening process is summarized in the study flow chart ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 1373 full-text reports were not accessible among the 25 full-text articles we assessed for eligibility, 18 studies were subsequently excluded. 3 , 6 , 8 , 10 , 12 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 Finally, 7 studies were included in a systematic review. 2 , 11 , 15 , 16 , 17 , 18 , 19 An overview of the search results and the screening process is summarized in the study flow chart ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lara-Carillo et al 12 also compared results between genders and found increased stimulated saliva flow in both gender groups, but with a higher initial flow rate in the male group. On the other hand, Kado et al 40 evaluated stimulated salivary flow between genders of pre-orthodontic patients and found a significantly higher flow rate in males than in females. These results were explained by the smaller size of salivary glands in females compared to males the influence of hormonal patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, the amount of saliva secreted decreases with age [8]. Moreover, the amount and properties of salivary secretions differ according to sex [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A study comparing oral hygiene in men and women reported that although men could have poorer oral hygiene compared to women, they showed better saliva test results and lower streptococcus mutans (S. mutans) counts [11].…”
Section: Introductionmentioning
confidence: 99%
“…The mean pH of saliva is 6.7, within the normal range of 6.2–7.6 [ 8 ]. The resting oral pH may vary between 5.0 and 9.0 depending on different factors, including age [ 9 ], gender [ 9 , 10 ], season, and even time of day [ 10 ]. Salivary pH alterations have been found in patients with various diseases, such as anorexia nervosa [ 11 ], gastroesophageal reflux disease [ 12 , 13 , 14 ], and diabetes mellitus [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%